2015
DOI: 10.1089/chi.2014.0129
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Obesity and Cognitive Performance in Children: A Longitudinal Study

Abstract: Background: The relationship between obesity and academic outcomes remains unclear. We evaluated the association between obesity and cognitive performance in US children.Methods: We analyzed two nationally representative prospective cohorts of children in the 1979 National Longitudinal Survey of Youth, ages 2 through 8 at baseline and followed for 6 years, from 1988 to 1994 (cohort 1, n = 2672) and 1994 to 2000 (cohort 2, n = 1991). The main exposure variable was obesity (defined as never obese, became obese, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…Ten articles assessed the association between obesity at baseline and academic achievement at follow-up [ 27 , 31 , 35 , 36 , 38 , 39 , 42 , 45 , 47 , 49 ].…”
Section: Part 1: Methods and Results Of The Systematic Reviewmentioning
confidence: 99%
“…Ten articles assessed the association between obesity at baseline and academic achievement at follow-up [ 27 , 31 , 35 , 36 , 38 , 39 , 42 , 45 , 47 , 49 ].…”
Section: Part 1: Methods and Results Of The Systematic Reviewmentioning
confidence: 99%
“…While not the focus of this systematic review, it is also possible that obesity and cognitive status are linked. There is inconsistent evidence that increased adiposity in children is associated with poorer neurocognitive functioning and academic performance, although the directionality of that relationship is not well understood ( Datar and Sturm, 2006 , Yau et al, 2012 , Liang et al, 2014 , Afzal and Gortmaker, 2015 ). Research has demonstrated an association between obesity and abnormalities in brain tissue; perhaps parts of the developing brain may be sensitive to the metabolic changes associated with excess adipose tissue ( Miller et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of longitudinal studies show inconsistent associations of overweight and obesity with cognition, except in adolescent girls [91]. However, a recent longitudinal study found no causal relationship between childhood obesity and cognitive performance [92]. Nevertheless, the results of one study suggested a positive relationship between body adiposity and academic achievement in children living in India, suggesting that excess energy intake may be better for brain development and learning than undernourishment [78].…”
Section: Overweight Obesity Cardiometabolic Risk and The Brainmentioning
confidence: 99%